The children's crusade : a novel - Packer, Ann, 1959- (Scribner, 2015)
"Bill Blair finds the land by accident, three wooded acres in a rustic community south of San Francisco. The year is 1954, long before anyone will call this area Silicon Valley. Struck by a vision of the family he has yet to create, Bill buys the property on a whim. In Penny Greenway he finds a suitable wife, a woman whose yearning attitude toward life seems compelling and answerable, and they marry and have four children. Yet Penny is a mercurial housewife, at a time when women chafed at the conventions imposed on them. She finds salvation in art, but the cost is high. Thirty years later, the three oldest Blair children, adults now and still living near the family home, are disrupted by the return of the youngest, whose sudden presence and all-too-familiar troubles force a reckoning with who they are, separately and together, and set off a struggle over the family's future. One by one, the siblings take turns telling the story--Robert, a doctor like their father; Rebecca, a psychiatrist; Ryan, a schoolteacher; and James, the malcontent, the problem child, the only one who hasn't settled down--their narratives interwoven with portraits of the family at crucial points in their history" --